Massive calcified tricuspid valve endocarditis in a patient with dual lumen tunneled venous catheter - Farag, Mina; Weymann, Alexander; Schmack, Bastian; Rauch, Helmut; Karck, Matthias; Szabó, Gábor (Annals of thoracic and cardiovascular surgery, 2014)
Infection is the most common cause of death in hemodialysis patients after cardiovascular complications. The long-term use of venous catheters for dialysis elevates the risk. Valvular calcification is of special concern in developing infective endocarditis and is often found in chronic dialysis patients. The right-sided endocarditis is rarely reported in the literature and may be overseen until the development of further complications. In our case tricuspid valve endocarditis, with severe insufficiency and stenosis due to a calcified laminar plate was found in a 57-year-old female patient undergoing dialysis due to end-stage renal disease. The calcification aroused from the tip of the dual lumen tunneled venous catheter used for routine dialysis. We replaced the tricuspid valve with mechanical valve prosthesis and reconstructed the right atrium.
Online: June 26, 2013
Gesehen am 04.03.2021